Makna Material Culture dalam “Sarung” sebagai Identitas Santri - Toto Sugiarto (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
In material culture as a concept of local culture and nation heritage, “sarong” also has non-material value, likes as a symbol of santri, heroism, social class, kindness and honor. Sarong with variuos size, color, motifs, and pattern shapes the person and society, even the identity of a nation, especially Indonesia. Sarong even became part of the symbol of religiosity and diversity of Indonesia. By borrowing Bung Karno's message that the task of future generations is nation character building, caring for and developing a sarong culture, it can be seen as an effort to care for and develop the nation's character. Therefore, this paper use approachs or perspectives : material culture concept, social class perspective, and nation characer building concept. Method of writing is literary studies and analysis content method by various in resorches that support this article. The result of exprloration indicate that sarong can be the symbol for nation building character and identity with meaning and history contents powerly.